A centralized/decentralized control approach for periodic systems with application to chromatographic separation processes. Issue 7 (2016) - Papathanasiou, Maria M.; Sun, Muxin; Oberdieck, Richard; Mantalaris, Athanasios; Pistikopoulos, Efstratios N.
Abstract: In this work we demonstrate the application of our recently presented PAROC framework and software platform for the development of a centralized/decentralized control strategy for the twin-column Multicolumn Solvent Gradient Purification Process (MCSGP) based on multi-parametric control policies. The derived controllers are tested under the presence of disturbances, while their stability is also assessed. The proposed control approach is evaluated under an in-silico, 'closed-loop' fashion against the process model. The designed controller captures efficiently the process setpoints, assuring optimal and stable operation during continuous mode.